Study of the Preparation of g-Glycidoxypropyltrimethoxysilane Film on Metallic Surface - Tan, Shiyu; Tian, Wanjie; Zhao, Shuo (Asian Journal of Chemistry, 2011)
Silylation is the process of surface treatment for metal or non-metal using solution of organic silicane. In this paper, the process of surface pretreatment with g-glycidoxypropyltrimethoxysilane (KH560) for stainless steel was studied. The results indicate that different process conditions (i.e., the type of hydrolytic reagent, the concentration of silane, hydrolysis time, aging temperature and time) all have effect on the properties of silane film. The optimum operation conditions using water/methanol/glycerin as hydrolytic reagent are the following: the concentration of silane is about 2 %, the hydrolysis time is 10 h, aging temperature is 120 ºC and aging time is 20 min. The time of corrosion resistance is more than 1 h in pitting corrosion test of CuSO4, which indicates good properties of silane film.